Preparing Medical Students with the Knowledge to Provide Telehealth in Underserved Communities - Ilia Dolouei; Ahmad Elhaija; Sophia Galstyan (Journal of Healthcare Solutions, 2025)
The COVID-19 pandemic led to an increase in the use of telehealth in the United States as it revealed the potential for this tool to foster more accessible healthcare (1). Although such adaptation of telehealth is advantageous in several ways, obstacles also exist that inhibit the proper implementation of telehealth practices. Through addressing and subsequently overcoming such obstacles, the pivotal role telehealth serves in bridging disparities in healthcare will be strengthened, enabling efficacy in bridging the existing disparities in healthcare. One such obstacle is educating future healthcare professionals regarding the barriers to telehealth, to contribute towards the development of a more equitable healthcare system (2). To accomplish this goal, we created a learning module focused on preparing medical students with knowledge regarding the shortcomings of telehealth in underserved communities with the objectives of advancing telehealth competency and ultimately providing solutions to increase accessibility (3). We developed a 30-minute asynchronous learning module highlighting the most prominent barriers to telehealth and revealing plausible solutions to reduce disparities amongst underserved communities (4). Through the International Healthcare Organization (IHO), the authors of this abstract emailed the module to medical students across various countries, including the United States of America, Bangladesh, and Armenia (5). The total sample size of this preliminary study included 30 medical students who completed the learning module, including a Pre-Assessment and Post-Survey. Based on the evaluations of the Post-Survey, 93.3% of students felt the learning module effectively taught the established goals of the study, and 93.3% of students agreed that the information provided could be successfully implemented in their future practice to promote healthcare equity. This learning module efficiently educated medical students regarding barriers to telehealth through its comprehensive review of existing circumstances and plausible solutions (6). It can therefore potentially serve as a foundation for medical students to contribute to successful telehealth implementations in their professional careers as they can implement their notable insights to lead by example as future physicians. This can ultimately broaden the module's impact in improving the telehealth landscape of underserved communities in the United States. ​ Works Cited​ ​ 1. HIMSS & Zoom. (2021). A virtual revolution: How the COVID-19 pandemic will transform care delivery. https://explore.zoom.us/docs/doc/Zoom_WP_A_Virtual_Revolution.pdf 2. Kuziemsky, C., Hunter, I., Udayasankaran, J. G., Ranatunga, P., Kulatunga, G., John, S., John, O., Flórez-Arango, J. F., Ito, M., Ho, K., Gogia, S. B., Araujo, K., Rajput, V. K., Meijer, W. J., & Basu, A. (2022). Telehealth as a means of enabling health equity. Yearbook of Medical Informatics, 31(1), 195–202. https://doi.org/10.1055/s-0042-1742500 ​ 3. Telehealth.HHS.gov. (2023, August 15). Health equity in telehealth. https://telehealth.hhs.gov/providers/health-equity-in-telehealth ​ 4. Latino Policy & Politics Institute. (2023, January 24). Equity gaps in telehealth use to manage chronic conditions during COVID-19. https://latino.ucla.edu/research/equity-gaps-telehealth-covid-19/ ​ 5. Elhaija, A., Sjogren-Black, C., Bhullar, S. “Examining Medical Care of Unhoused Individuals in the Skid Row Community.” Journal of Healthcare Solutions, 2025. ​ 6. Haimi, M. (2023). The tragic paradoxical effect of telemedicine on healthcare disparities—a time for redemption: A narrative review. BMC Medical Informatics and Decision Making, 23(1), 95. https://doi.org/10.1186/s12911-023-02194-4